2007
DOI: 10.1111/j.1745-7254.2007.00679.x
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and development of sulforaphane as a cancer chemopreventive phytochemical

Abstract: Sulforaphane (SF) is a phytochemical that displays both anticarcinogenic and anticancer activity. SF modulates many cancer-related events, including susceptibility to carcinogens, cell death, cell cycle, angiogenesis, invasion and metastasis. We review its discovery and development as a cancer chemopreventive agent with the intention of encouraging further research on this important compound and facilitating the identification and development of new phytochemicals for cancer prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
159
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 197 publications
(162 citation statements)
references
References 121 publications
3
159
0
Order By: Relevance
“…SUL is a well-known chemopreventive phytochemical, capable of activating Nrf2-regulated cytoprotective signaling pathway. 33 Our results showed that SUL induced upregulation of NQO1 in an Nrf2-dependent manner, however, Nrf2 activation by SUL does not lead to induction of GCLC and GSS, even though GCLC gene promoter is known to carry a functional ARE. Similar modulation of these phase II enzymes was observed during keratinocyte differentiation as well.…”
Section: Effect Of Nrf2 Knockout On Als Mice Y Guo Et Almentioning
confidence: 78%
“…SUL is a well-known chemopreventive phytochemical, capable of activating Nrf2-regulated cytoprotective signaling pathway. 33 Our results showed that SUL induced upregulation of NQO1 in an Nrf2-dependent manner, however, Nrf2 activation by SUL does not lead to induction of GCLC and GSS, even though GCLC gene promoter is known to carry a functional ARE. Similar modulation of these phase II enzymes was observed during keratinocyte differentiation as well.…”
Section: Effect Of Nrf2 Knockout On Als Mice Y Guo Et Almentioning
confidence: 78%
“…Sulforaphane is a glucosinolate derivative that has been widely studied for its anticancer activity [4,7]. Sulforaphane has been demonstrated to induce phase II detoxification and antioxidant enzymes [8] and to inhibit phase I enzymes that activate pro-carcinogens [9].…”
Section: Introductionmentioning
confidence: 99%
“…Administration of sulforaphane inhibits and/or retards tumorigenesis induced by carcinogens in animal models [10,11]. In addition to its preventive effect on cancer, sulforaphane has recently been shown to inhibit the growth of various types of cancer cells by modulating multiple pathways related to cancer progression [7,12]. …”
Section: Introductionmentioning
confidence: 99%
“…Sulforaphane (SFN) is the most characterized ITC compound and has been identified as the most active ITC homologue (Zhang and Tang, 2007). Since it was first identified in the early 1990s, SFN has been well studied as a chemopreventive agent for cancer.…”
Section: Introductionmentioning
confidence: 99%